Pengaruh penguasaan cermin terhadap hasil belajar fisika materi pokok cahaya kelas XII SMA Negeri 7 Padangsidimpuan - Siregar, Mariana; Nasution, S.Pd., M.Pd, Febriani Hastini (Jurnal Physics Education (PhysEdu), 2024)
The aim of this research was to know whether there was a significant influence between mirror mastery on student’s achievement in light subject at twelfth grade student’s of SMA Negeri 7 Padangsidimpuan. The population of this research was all the twelfth grade students of SMA Negeri 7 Padangsidimpuan which include 3 classes or 75 students. By applying total sampling techbique, the writer took 101 students as the sample. In colleting the data, the writer used test. Based on the result of this research, mirror mastery had the average 53,20, it was categorized “fair”. While the students achievement in light subject had the average 61,70, it was categorized “enough”. Based on statistics analysis calcution, it could be gotten rcount = 0,622, in error level significant 5%, confident level significant 95%, df = N – 2 = 75-2=73. it could be gotten that ttable = 0,228. It could be seen that tcount was greater ttable (0,622>0,228). The alternative hypothesis was accepted. It maens that there was a significant influence between mirror mastery on students achievement in light subject at the twelfth grade students of SMA Negeri 7 padangsidimpuan